Bousigonine A and B, bis- and tri-indole alkaloids from Bousigonia mekongensis and their preventing high glucose-induced podocyte injury activity. Issue 37 (12th September 2019) - Wang, Ya-Lan; Guo, Chang-Run; Mu, Yan; Lin, Yun-Liang; Yan, Hui-Jiao; Wang, Zhi-Wei; Wang, Xiao-Jing
Graphical abstract: Highlights: Two novel bis- and tri-indole alkaloids were isolated from B. mekongensis . The absolute configurations of1 and2 were established. Their activity of preventing high glucose-induced podocyte injury was evaluated. Abstract: Bousigonine A (1 ), an unprecedented eburnamine-voaphylline type dimeric indole alkaloid, and Bousigonine B (2 ), the first example of eburnamine-eburnamine-aspidospermine type trimeric indole alkaloid were isolated from Bousigonia mekongensis . Their structures were elucidated mainly by spectroscopic analysis and compared to published data. Their preventing high glucose-induced podocyte injury activity were evaluated for the first time, and compound1 exhibited significant effect with EC50 value of 2.5 μM.